US Migration Policy Towards the States of the North American Continent - I. P. Tsapenko (MGIMO University Press, 2021)
The article aims at characterizing the content, problems, and consequences of the US interaction with the countries of the North American continent in the sphere of migration. The objective is to identify the main directions and assess the prospects for the overdue reform of the US regional migration policy. The author examines migration policy in the framework of NAFTA-USMCA and multi-vector initiatives aimed at managing movements within the region.The results show that migration on the continent, primarily from Mexico and Central America to the United States, is characterized by a high level of regionalization. Due to massive spontaneous flows of migrants who lack the required documents for entering, staying, and working in the country of destination, including asylum seekers, the region's countries face serious challenges aggravated by the pandemic. The US cooperates in various forms and directions with the region's countries in the sphere of migration. It includes limited liberalization of specific categories of specialists and business representatives from the three member-states of the NAFTA-USMCA. Nevertheless, such interaction focuses on curbing the inflow of migrants without documents to the United States, which makes these relations asymmetric along the center-periphery axis. Such a policy is inconsistent and leads to acute humanitarian crises on the borders of the region's states. The administration of Joe Biden faces difficulties in reforming migration policy during the pandemic and growing public concern. The issue urges regional cooperation on a fairer and more equitable basis; otherwise, it is impossible to advance towards the promotion of legal migration.